2019
DOI: 10.1126/sciadv.aaw0315
|View full text |Cite
|
Sign up to set email alerts
|

Fc receptor–like 1 intrinsically recruits c-Abl to enhance B cell activation and function

Abstract: B cell activation is regulated by the stimulatory or inhibitory co-receptors of B cell receptors (BCRs). Here, we investigated the signaling mechanism of Fc receptor-like 1 (FcRL1), a newly identified BCR co-receptor. FcRL1 was passively recruited into B cell immunological synapses upon BCR engagement in the absence of FcRL1 cross-linking, suggesting that FcRL1 may intrinsically regulate B cell activation and function. BCR cross-linking alone led to the phosphorylation of the intracellular Y281ENV motif of FcR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(34 citation statements)
references
References 42 publications
(61 reference statements)
1
29
2
Order By: Relevance
“…Fc receptor-like 1 ( FCRL1 ) is a novel B cell receptor (BCR) co-receptor. Zhao et al ( 38 ) revealed a vital BCR signal enhancement role of FCRL1 via its internal B cell immune synapse recruitment and subsequent c-Abl recruitment on BCR cross-linking. Furthermore, KEGG and GO analyses expressed that the genes were enriched in the immune response pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Fc receptor-like 1 ( FCRL1 ) is a novel B cell receptor (BCR) co-receptor. Zhao et al ( 38 ) revealed a vital BCR signal enhancement role of FCRL1 via its internal B cell immune synapse recruitment and subsequent c-Abl recruitment on BCR cross-linking. Furthermore, KEGG and GO analyses expressed that the genes were enriched in the immune response pathway.…”
Section: Discussionmentioning
confidence: 99%
“…It is noteworthy that FcRL1 was upregulated in Memory B only from severe convalescent COVID-19 patients. There is a study shows that FcRL1 enhances B cell activation and function [41]. In another panel of genes relevant to humoral immune response, we found two molecules S100A8 and S100A9 upregulated in Plasma B only from severe subjects.…”
Section: Dual Functions Of B Cell Subsets In Convalescent Covid-19 Patientsmentioning
confidence: 62%
“…However, another study showed that within 6 to 10 weeks of SARS-COV-2 infection, the level of (RBD)-speci c IgG speci c to the receptor domain decreased [71], indicating that B lymphocytes have dual functions during the recovery phase. A recent study reported key roles of Fc receptor-like 1 (FCRL1), a newly identi ed BCR co-receptor speci cally expressed on the surface of B cells, in antibody production unveiled by experiment showing that FcRL1-de cient mice exhibited markedly impaired formation of extrafollicular plasmablasts and germinal centers, along with decreased antibody production upon antigen stimulation [41]. In our study, we found that the expression of FCRL1, a gene related to B cell activation, was signi cantly increased in patients with moderate recovery, suggesting that B cell function was activated.…”
Section: T Cells and B Cells Play Critical Roles In Clearing Viral Infections And Immunological T And B Cell Memorymentioning
confidence: 99%
“…It is noteworthy that FcRL1 was upregulated in Memory B only from severe convalescent COVID-19 patients. A study showed that FcRL1 enhances B cell activation and function [41] . In another panel of genes relevant to humoral immune response, we found two molecules S100A8 and S100A9 upregulated in Plasma B only from severe subjects.…”
Section: Resultsmentioning
confidence: 99%